2022
DOI: 10.1111/resp.14339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic mucus hypersecretion on treatment responses to inhaled therapies in patients with chronic obstructive pulmonary disease: Post hoc analysis of the IMPACT trial

Abstract: Background and objective Chronic mucus hypersecretion (CMH) is a clinical phenotype of COPD. This exploratory post hoc analysis assessed relationship between CMH status and treatment response in IMPACT. Methods Patients were randomized to once‐daily fluticasone furoate/umeclidinium/vilanterol (FF/UMEC/VI) 100/62.5/25 μg, FF/VI 100/25 μg or UMEC/VI 62.5/25 μg and designated CMH+ if they scored 1/2 in St George's Respiratory Questionnaire (SGRQ) questions 1 and 2. Endpoints assessed by baseline CMH status includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…5 Thompson et al observed in symptomatic COPD patients, FF/UMEC/VI, when compared with FF/VI and UMEC/VI, reduced exacerbation rates, improved health status and lung function irrespective of whether the subjects had concomitant CMH. 6 No obvious differences in pneumonia were observed for FF/UMEC/VI in the groups of patients with or without CMH. Though the presence of CMH had no effect on the efficacy and safety of FF, UMEC and VI in this study, it is uncertain if this is true for other brands of inhaled corticosteroids (ICS), longacting beta-agonists (LABA) and long-acting antimuscarinic agents (LAMA).…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…5 Thompson et al observed in symptomatic COPD patients, FF/UMEC/VI, when compared with FF/VI and UMEC/VI, reduced exacerbation rates, improved health status and lung function irrespective of whether the subjects had concomitant CMH. 6 No obvious differences in pneumonia were observed for FF/UMEC/VI in the groups of patients with or without CMH. Though the presence of CMH had no effect on the efficacy and safety of FF, UMEC and VI in this study, it is uncertain if this is true for other brands of inhaled corticosteroids (ICS), longacting beta-agonists (LABA) and long-acting antimuscarinic agents (LAMA).…”
mentioning
confidence: 89%
“…Thompson et al observed in symptomatic COPD patients, FF/UMEC/VI, when compared with FF/VI and UMEC/VI, reduced exacerbation rates, improved health status and lung function irrespective of whether the subjects had concomitant CMH 6 . No obvious differences in pneumonia were observed for FF/UMEC/VI in the groups of patients with or without CMH.…”
mentioning
confidence: 96%
See 3 more Smart Citations